2019
DOI: 10.1016/j.biortech.2018.10.081
|View full text |Cite
|
Sign up to set email alerts
|

Arthrospira maxima OF15 biomass cultivation at laboratory and pilot scale from sugarcane vinasse for potential biological new peptides production

Abstract: . Arthrospira maxima OF15 biomass cultivation at laboratory and pilot scale from sugarcane vinasse for potential biological new peptides production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(31 citation statements)
references
References 44 publications
0
31
0
Order By: Relevance
“…Another study, conducted by Yamaguchi and Koketsu [ 19 ], showed that Nostochopsis lobatus MAC0804NAN produced a large amount of polysaccharides with a high inhibitory effect (IC 50 = 7.18 µg/mL). It was also reported that an Arthrospira -derived peptide may be involved in hyaluronidase inhibition [ 43 ]. Together, these results support the potential of cyanobacteria compounds and extracts as anti-aging ingredients for cosmeceutical applications.…”
Section: Resultsmentioning
confidence: 99%
“…Another study, conducted by Yamaguchi and Koketsu [ 19 ], showed that Nostochopsis lobatus MAC0804NAN produced a large amount of polysaccharides with a high inhibitory effect (IC 50 = 7.18 µg/mL). It was also reported that an Arthrospira -derived peptide may be involved in hyaluronidase inhibition [ 43 ]. Together, these results support the potential of cyanobacteria compounds and extracts as anti-aging ingredients for cosmeceutical applications.…”
Section: Resultsmentioning
confidence: 99%
“…Arthrospira maxima is another example of cyanobacteria able to produce anti-collagenase peptides. The peptide fraction PHS showed anti collagenase activity (92.5%) with an IC 50 of 32.5 mg/ mL compared with the synthetic inhibitor (57.13%) 42 . These peptides sequence can resemble the cleavage site in native collagen, and thus prevent the degradation of the ECM.…”
Section: Collagenasesmentioning
confidence: 95%
“…Chlorella accumulate high concentrations of carotenoids (astaxanthin, lutein, β-carotene, violaxanthin and zeaxanthin), antioxidants, vitamins, polysaccharides, proteins, peptides and fatty acids [5,38]. In addition to all the benefits mentioned, the bioactive compounds of microalgae can have a biological, immune, antiviral and anti-cancer properties, being highly active [39].…”
Section: Application Of Microalgaementioning
confidence: 99%